Model Pembelajaran Kelas Praktek Conversation (Percakapan) Pada Masa Pandemi Bagi Mahasiswa D3 Fakultas Ekonomi Dan Bisnis Universitas Udayana - Ni Ketut Sri Rahayuni (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2023)
Through this research process, it is hoped that the most appropriate and effective learning model can be developed in a conversation practice class at the Faculty of Economics and Business. It is hoped that the results of this research will provide a general idea for the English course teaching teams in all faculties regarding the appropriate learning process in guiding students so that they can then apply it directly both in lectures and in accordance with the pandemic period when they have to study from home.